Graphene oxide/polyvinylpyrrolidone-doped MoO3 nanocomposites used for dye degradation and their antibacterial activity: a molecular docking analysis - Ikram, Muhammad; Atiq, Iram; Rafiq Butt, Alvina; shahzadi, Iram; Ul-Hamid, Anwar; Haider, Ali; Nabgan, Walid; Medina, Francisco (Frontiers in Chemistry, 2023)
In this study, MoO3 nanostructures were prepared, doped with various concentrations of graphene oxide (2 and 4% GO) and a fixed amount of polyvinylpyrrolidone (PVP) using the co-precipitation method. The motive of this study was to examine the catalytic and antimicrobial efficacy with evidential molecular docking analyses of GO/PVP-doped MoO3. GO and PVP were utilized as doping agents to reduce the exciton recombination rate of MoO3 by providing more active sites that increase the antibacterial activity of MoO3. The prepared binary dopant (GO and PVP)-dependent MoO3 was used as an effective antibacterial agent against Escherichia coli (E. coli). Notably, 4% GO/PVP-doped MoO3 showed good bactericidal potential against E. coli at higher concentrations in comparison to ciprofloxacin. Furthermore, in silico docking revealed the possible inhibitory impact of the synthesized nanocomposites on folate and fatty acid synthesis enzymes, dihydrofolate reductase and enoyl-[acyl carrier protein] reductase, respectively.